The Effectiveness of Compilation of Islamic Law in Resolving Inheritance Disputes at the Religious Courts of Panyabungan and Padang Sidempuan City - Muhammad Fadlan Is; Defel Fakhyeldi; Azizatur Rahmah (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2022)
Debate and rejection of some of the Compilation of Islamic Law (KHI) materials regarding inheritance always occur among Indonesian Muslims. Not all provisions in KHI can be accepted by society, especially by Muslims in Panyabungan and Padangsidimpuan City. Several